Wave motion in elastic solids - Graff, Karl F. (Dover Publications, 1991)
Comprehensive, self-contained coverage of a variety of topics ranges from the elementary theory of waves and vibrations in strings to three-dimensional theory of waves in thick plates. Emphasis on analytical and experimental results, in addition to theoretical development. Appendices contain introductory material on elasticity, transforms, experimental techniques. Over 100 problems.
Originally published: London : Oxford University Press, 1975.
Keywords: Solids.; Elastic waves.; elektronické knihy; electronic books